Identification of the Extractives Chemical Compounds in Newsprint by GC/MS Methods - Vaysi, Ramin (Asian Journal of Chemistry, 2011)
In this work, paper samples were chosen randomly from paper newsprint produced in Mazandaran Pulp and Paper Mill. At first stage, the paper flour provided and then measured extractive per cent by the TAPPI standard methods. The results showed that average of extractives was 6.92 % in newsprint. In the second stage, paper flour washed by toluene-ethyl alcohol with the 2:1 ratio and added BSTFA to extractives residue. Then the samples kept in Ben Marry Bath in 70 ºC for 1 h and they were analyzed by GC/MS. Finally, the GC diagram was used for identification of the compounds; it shows the abundance and retention time of each compound and calculation of quartz index and Adams table. Generally, 58 compounds definitely present in newsprint. The benzaldehyde (32.56 %), trimethyl silane (12.65 %), bis(2-ethylhexyl)phthalate (6.98 %), γ- sitosterol (4.84 %), n-hexadecanoic acid (4.56 %), dibenzyl (3.82 %) were the main compounds and the dodecanoic acid (0.14 %), decane (0.18 %), xylene (0.19 %), 1-methyl-4-phenylmethyl benzene (0.2 %) were present in low amount, respectively.